Aspects of Theory of Mind that attenuate the relationship between persecutory delusions and social functioning in schizophrenia spectrum disorders. (September 2017) - Phalen, Peter L.; Dimaggio, Giancarlo; Popolo, Raffaele; Lysaker, Paul H.
Abstract: Background and objectives: Despite the apparent relevance of persecutory delusions to social relationships, evidence linking these beliefs to social functioning has been inconsistent. In this study, we examined the hypothesis that theory of mind moderates the relationship between persecutory delusions and social functioning. Methods: 88 adults with schizophrenia or schizoaffective disorder were assessed concurrently for social functioning, severity of persecutory delusions, and two components of theory of mind: mental state decoding and mental state reasoning. Mental state decoding was assessed using the Eyes Test, mental state reasoning using the Hinting Task, and social functioning assessed with the Social Functioning Scale. Moderation effects were evaluated using linear models and the Johnson-Neyman procedure. Results: Mental state reasoning was found to moderate the relationship between persecutory delusions and social functioning, controlling for overall psychopathology. For participants with reasoning scores in the bottom 78th percentile, persecutory delusions showed a significant negative relationship with social functioning. However, for those participants with mental state reasoning scores in the top 22nd percentile, more severe persecutory delusions were not significantly associated with worse social functioning. Mental state decoding was not a statistically significant moderator. Limitations: Generalizability is limited as participants were generally men in later phases of illness. Conclusions: Mental state reasoning abilities may buffer the impact of persecutory delusions on social functioning, possibly by helping individuals avoid applying global beliefs of persecution to specific individuals or by allowing for the correction of paranoid inferences. Highlights: It is unknown what factors affect the link between paranoia and social functioning. We assessed paranoia and social functioning in adults with psychotic disorders. We then tested two ToM skills: mental state reasoning and mental state decoding. Mental state reasoning moderated effect of persecutory delusions on functioning.